Soil properties and produce quality of cardamom under organic farming - Arun G (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 2004)
An investigation was conducted at the Upputhara panchayath of Peermede taluk, in Idukki district of Kerala with the objective to compare the soil properties, crop nutrient concentrations and quality of cardamom (Elettaria cardamomum Maton) under organic and conventional farming.' Nine certified organic farms, that follow IMO and Skal International certification standards and eight adjacent conventional cardamom farms following recommendations of Spices Board were selected for investigation. Fifty samples each of soil and cardamom leaves were drawn from both organic and conventional farms. Cured cardamom samples were collected from each farm under study. A proforma was developed in accordance with the standards fixed by IFOAM for documenting farming practices of the study area Biometric parameters and yield attributes of cardamom plants were observed directly and yield data for the organic and conventional cardamom farms were collected from farm records during the survey. The orgaruc farms selected for the study did not follow strict package of practices and there were variations among individual farms, but within the purview of certification procedures. Conventional and organic farming practices of the study area differed mainly on fertilization policy, plant protection strategy, weed control and land management. Soils of the organic cardamom farms were found to have better aeration than conventional farms, evident from the significantly lower bulk density of soils of the organic farrns. Another significant effect of organic agriculture in cardamom was the improvement of soil electrochemical properties. The rich organic soils of the study area resulted in insignificant difference in organic carbon and organic matter content of the soils of the two farming systems. The ranges of major nutrients in soils were medium to high and hence the difference between organic and conventional cardamom farms with respect to major nutrients was also not consistent. Microbes were proliferating in the organic farms resulting in